ChemInform Abstract: The Modified Trifluoromethylation Protocol Applicable to Electronically Deficient Iodopyridinones. Issue 52 (10th December 2015) - Kawasaki‐Takasuka, Tomoko; Yamazaki, Takashi
Abstract: The utility of this method is demonstrated in the synthesis of pharmaceutically interesting pirfenidone analogue (XVI).